2014
DOI: 10.1155/2014/728564
|View full text |Cite
|
Sign up to set email alerts
|

Wavelets Application in Prediction of Friction Stir Welding Parameters of Alloy Joints from Vibroacoustic ANN-Based Model

Abstract: This paper analyses the correlation between the acoustic emission signals and the main parameters of friction stir welding process based on artificial neural networks (ANNs). The acoustic emission signals inZandYdirections have been acquired by the AE instrument NI USB-9234. Statistical and temporal parameters of discomposed acoustic emission signals using Wavelet Transform have been used as input of the ANN. The outputs of the ANN model include the parameters of tool rotation speed and travel speed, and tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Mishra et al [13] implemented the Convolutional Neural Network for identification of the texture of Friction Stir Welded joints and Conventional Welded joints. Macias et al [14] established a correlation between the acoustic emission signals and the various main parameters of friction stir welding process based on artificial neural networks (ANNs) trained on Levenberg-Marquardt algorithm. Figure 13 and 14 shows the methodology and the development of Artificial Neural Network architecture respectively.…”
Section: Actual Uts (Mpa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mishra et al [13] implemented the Convolutional Neural Network for identification of the texture of Friction Stir Welded joints and Conventional Welded joints. Macias et al [14] established a correlation between the acoustic emission signals and the various main parameters of friction stir welding process based on artificial neural networks (ANNs) trained on Levenberg-Marquardt algorithm. Figure 13 and 14 shows the methodology and the development of Artificial Neural Network architecture respectively.…”
Section: Actual Uts (Mpa)mentioning
confidence: 99%
“…Artificial Neural Network development methodology[14] Artificial Neural Network architecture[14] Figure 15 shows the predicted and measured results on the given dataset. It is clearly observed that the results obtained from the new model obtained, based on Neural Network architecture is an effective technique for the prediction of Friction Stir Welding process parameters and tensile strength of joint.…”
mentioning
confidence: 99%